2022
DOI: 10.3390/jof8070722
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review to Assess the Relationship between Disseminated Cerebral Aspergillosis, Leukemias and Lymphomas, and Their Respective Therapeutics

Abstract: Disseminated disease following invasive pulmonary aspergillosis (IPA) remains a significant contributor to mortality amongst patients with hematologic malignancies (HMs). At the highest risk of mortality are those with disseminated disease to the central nervous system, known as cerebral aspergillosis (CA). However, little is known about the risk factors contributing to disease amongst HM patients. A systematic review using PRISMA guidelines was undertaken to define HM patient subgroups, preventative measures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Studying disseminated aspergillosis in the context of corticosteroid use is clinically relevant, given that 25%–50% of patients with CA are being treated with corticosteroids for hematological malignancies, graft versus host disease, or transplant therapy ( 17 , 18 ). However, we found that corticosteroid-treated mice were highly susceptible to intravenous challenge with A. fumigatus but interexperimental variability made this model untenable to evaluate the pathogenesis of CA.…”
Section: Resultsmentioning
confidence: 99%
“…Studying disseminated aspergillosis in the context of corticosteroid use is clinically relevant, given that 25%–50% of patients with CA are being treated with corticosteroids for hematological malignancies, graft versus host disease, or transplant therapy ( 17 , 18 ). However, we found that corticosteroid-treated mice were highly susceptible to intravenous challenge with A. fumigatus but interexperimental variability made this model untenable to evaluate the pathogenesis of CA.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent systematic review, we identified acute myeloid leukemia (AML) as the primary hematologic malignancy associated with CA disseminating from IPA ( 27 ). The induction chemotherapy often employed in AML is a “7 + 3” regimen with the chemotherapeutic drugs cytarabine and daunorubicin (both drugs administered for the first 3 days, with cytarabine alone given for an additional 4 days) ( 28 ).…”
Section: Resultsmentioning
confidence: 99%